The Role of rs4626 and rs7221352 Polymorphisms on the TOB1 Gene in Turkish Relapsing-Remitting Multiple Sclerosis Patients - Fulya Başoğlu Köseahmet; Candan Eker; Musa Öztürk; Şebnem Özdemir; Ayhan Köksal; Savim Baybaş; Tuba Günel (European Journal of Biology)
Objective: Multiple sclerosis often causes neurological disability and reduced quality of life. Genetic biomarkers are important tools for the diagnosis and prognoses of diseases. This study has been conducted to explore the haplotype frequencies formed by rs4626 and rs7221352 single-nucleotide polymorphisms (SNPs) in the coding region variant (rs4626) and 5' upstream region intron variant (rs7221352) of the transducer of the ERBB2.1 (TOB1) gene in individuals with relapsing remitting multiple sclerosis. Materials and Methods: Thirty patients with an Expanded Disability Status Scale (EDSS) score<3, 30 patients with EDSS≥5, and 30 healthy controls participated in the study. The TOB1 rs4626 T/C and rs7221352 G/A single-base variations were applied using the quantitative real-time polymerase chain reaction method in accordance with the TaqMan SNP Genotyping Assays instructions. Results: The genotype frequencies of TOB1 rs4626 TT/TC/CC were respectively 3.3%, 53.3%, and 43.3% in the EDSS<3 cases and 10%, 53.3%, and 36.7% in the EDSS≥5 cases. The genotype frequencies of TOB1 rs7221352 GG/AG/AA were respectively 3.3%, 86.7%, and 10% in the EDSS<3 cases and 10%, 70%, and 20% in the EDSS≥5 cases. With respect to the estimated values in the study cohort, allelic variant frequency was higher in the patient group for both SNP variants (p<0.001). Conclusion: The presence of variant alleles in the rs4626 and rs7221352 polymorphisms in TOB1 may have a role in the disease immunopathogenesis. Further investigations involving larger groups are required to understand the effects of TOB1.